ANALISIS IMPLEMENTASI STRATEGI PROMOSI KESEHATAN PERSALINAN OLEH TENAGA KESEHATAN DI PUSKESMAS TABARINGAN KOTA MAKASSAR - Sari M, Laras Widya; Yusuf, Andi; Nurfaizah, Sitti (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2024)
Childbirth assisted by health workers is one of the indicators of Minimum Service Standards (SPM). As the spearhead in realizing a healthy Indonesia and the center for community health development, Community Health Centers must prioritize promotion and prevention where in providing services a strategy is needed to improve efforts to provide excellent service, including advocacy, social support, and community empowerment. This research aims to find out how the related aspects, advocacy, empowerment and social support are implemented in efforts to achieve births assisted by health workers. This research approach uses a qualitative method with a qualitative descriptive method. Implementation related to advocacy has been carried out by implementing regulatory policies from the city health service, and internal health center policies in the form of SK letters and appointing people in charge of the delivery achievement program. An obstacle to the implementation of advocacy is the lack of adequate human resources which results in less than optimal programs being implemented. implementation of community empowerment programs including home visits, providing active education during posyandu activities, cadre training programs held annually to maximize the implementation of empowerment in the community, as well as repeated monitoring held by the community health center in order to obtain data and information related to pregnancy, childbirth and post birth. The high mobility of the local community, the busyness and distance of cadres in monitoring, the lack of full awareness of pregnant women in checking themselves and the persistence of several beliefs related to myths among pregnant and postnatal women are some of the obstacles in empowerment efforts. Regarding the social aspect, support is currently going well with the support and response of local community leaders in accepting and actively participating in supporting the community health center program efforts. Suggestions for Tabaringan Community Health Center in their efforts to implement health promotion strategies include actively involving the community so that people are willing and aware to prosper themselves independently, as well as providing adequate human resources so that the implementation of activity programs can run optimally.